Thoracolumbar spine loading associated with kinematics of the young and the elderly during activities of daily living. (21st March 2018) - Ignasiak, Dominika; Rüeger, Andrea; Sperr, Ramona; Ferguson, Stephen J.
Abstract: Excessive mechanical loading of the spine is a critical factor in vertebral fracture initiation. Most vertebral fractures develop spontaneously or due to mild trauma, as physiological loads during activities of daily living might exceed the failure load of osteoporotic vertebra. Spinal loading patterns are affected by vertebral kinematics, which differ between elderly and young individuals. In this study, the effects of age-related changes in spine kinematics on thoracolumbar spinal segmental loading during dynamic activities of daily living were investigated using combined experimental and modeling approach. Forty-four healthy volunteers were recruited into two age groups: young (N = 23, age = 27.1 ± 3.8) and elderly (N = 21, age = 70.1 ± 3.9). The spinal curvature was assessed with a skin-surface device and the kinematics of the spine and lower extremities were recorded during daily living tasks (flexion–extension and stand-sit-stand) with a motion capture system. The obtained data were used as input for a musculoskeletal model with a detailed thoracolumbar spine representation. To isolate the effect of kinematics on predicted loads, other model properties were kept constant. Inverse dynamics simulations were performed in the AnyBody Modeling System to estimate corresponding spinal loads. The maximum compressive loads predicted for the elderly motion patterns were lower than those of the young for L2/L3 and L3/L4 lumbar levels during flexion and for upper thoracic levels during stand-to-sit (T1/T2–T8/T9) and sit-to-stand (T3/T4–T6/T7). However, the maximum loads predicted for the lower thoracic levels (T9/T10–L1/L2), a common site of vertebral fractures, were similar compared to the young. Nevertheless, these loads acting on the vertebrae of reduced bone quality might contribute to a higher fracture risk for the elderly.